Increased levels of α4-containing GABAA receptors in focal cortical dysplasia: A possible cause of benzodiazepine resistance. (September 2021) - Sharma, Devina; Dixit, Aparna Banerjee; Dey, Soumil; Tripathi, Manjari; Doddamani, Ramesh; Sharma, M.C.; Lalwani, Sanjeev; Gurjar, Hitesh Kumar; Chandra, P. Sarat; Banerjee, Jyotirmoy
Abstract: Benzodiazepines are the first choice of anti-epileptic drugs used to treat seizures. However, it has been seen that their efficacy decreases with time leading to drug insensitivity, plausibly caused by an alteration in the expression of the benzodiazepine biding site on GABAA receptors. This study was designed to investigate if the differential expression of GABAA receptor subunits α1/α4/γ2/δ across the postsynaptic sites could contribute to benzodiazepine resistance in patients with focal cortical dysplasia (FCD), the most common cause of drug resistant epilepsy in pediatric population. Differential gene and cellular expression of GABAA receptor subunits α1, α4, γ2 and δ were evaluated and validated using qPCR and immunohistochemistry. Whole cell patch clamp studies were performed on pyramidal neurons of resected cortical FCD samples to measure the spontaneous GABAA receptor activity. Upregulation of α4-and γ2-subunits containing GABAA receptors were observed at both mRNA and protein level. α1-and δ-subunits containing GABAA receptors did not show any significant changes. Flumazenil treatment did not affect the kinetics of GABAergic events in FCD; however, it significantly reduced the frequency and amplitude of spontaneous GABAergic activity in non-seizure control samples. Our results demonstrate the enhanced expression of α4-containing GABAA receptors and GABAergic activity in pyramidal neurons which in turn may contribute to benzodiazepine resistance in FCD patients. Graphical abstract: Image 1 Highlights: Significant upregulation of α4- and γ2-containing GABAA  receptor expression in patients with FCD. GABAergic activity in FCD remains unaltered by flumazenil suggesting alteration in the benzodiazepine binding site. Increased expression of α4-containing GABAA  receptors could be associated with benzodiazepine resistance.